Kemampuan pemahaman konsep matematis peserta didik kelas v pada materi akar pangkat tiga - Hasanudin Hasanudin; Iyam Maryati (Jurnal Inovasi Pembelajaran Matematika: PowerMathEdu, 2023)
Understanding the concept is a very important aspect in learning, because students understand the concept so they can develop their abilities in each subject. The aim of the research is to analyze students' ability to understand mathematical concepts. The method applied in this study was descriptive method. The research subjects were fifth grade students. The instrument used in this research was a test of students' mathematical concept understanding ability, which totaled 4 questions according to indicators of students' understanding of mathematical concepts. After data collection, the researcher analyzed the results of working on the ability to understand mathematical concepts and the results of the interviews to see the ability to understand students' mathematical concepts. Based on data analysis, it can be concluded that the ability to understand mathematical concepts in class V students at SDIT PERSIS Tarogong is still low, as evidenced by the presence of errors in solving mathematical comprehension ability questions, especially on indicators of using, utilizing, choosing certain procedures or operations and applying concepts or problem-solving algorithms in cube root material.Pemahaman konsep merupakan suatu aspek yang sangat penting dalam pembelajaran, karena siswa memahami konsep maka mereka dapat mengembangkan kemampuannya dalam setiap mata pelajaran. Tujuan  penelitian    adalah    menganalisis  kemampuan  pemahaman  konsep matematis siswa.  Metode  yang diterapkan  dalam  penelitian  ini  yaitu  metode deskriptif  Subjek  penelitiannya  adalah  siswa  kelas V. Instrumen yang digunakan dalam penelitian ini adalah tes kemampuan pemahaman konsep matematis siswa yang berjumlah 4 soal sesuai dengan indikator pemahaman konsep matematis siswa. Setelah pengumpulan data, peneliti menganalisis hasil pengerjaan  soal kemampuan pemahaman konsep matematis dan hasil wawancara untuk melihat kemampuan pemahaman konsep matematis siswa. Berdasarkan analisis data dapat disimpulkan bahwa kemampuan pemahaman konsep matematis siswa  kelas V SDIT PERSIS Tarogong masih rendah  yang  dibuktikan  dengan  terdapatnya  masih ada   kesalahan  menyelesaikan soal kemampuan pemahaman matematis terutama pada indikator menggunakan, memanfaatkan, memilih prosedur atau operasi tertentu dan mengaplikasikan konsep atau algoritma pemecahan masalah  dalam materi akar pangkat tiga.